Medical education - competency based medical education - how far, how near - moving from rote learning to artificial intelligence - part 1 - N.K. Gupta; Uma Gupta (Al Ameen Medical College, 2023)
Education has been important in human life since time immemorial. It has witnessed and assimilated changes with time. Word education is derived from Latin word Educatio, consisting of two words" e" (from, out) and "duco" (I lead OR I conduct) - which has many meaning like - I lead forth, I take out, I raise up. Education encompasses many fields so defined accordingly. From process to product. It ranges from an improvement in the learners to not assigning any value to it. At present, it means multiple changes may be multiple times to make it learner centered and outcome based, to make competent Indian medical graduate